2015
DOI: 10.1016/j.cels.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Driving Innovation in Health Systems through an Apps-Based Information Economy

Abstract: Healthcare data will soon be accessible using standard, open software interfaces. Here, we describe how these interfaces could lead to improved healthcare by facilitating the development of software applications (apps) that can be shared across physicians, health care organizations, translational researchers, and patients. We provide recommendations for next steps and resources for the myriad stakeholders. If challenges related to efficacy, accuracy, utility, safety, privacy, and security can be met, this emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 17 publications
0
70
0
2
Order By: Relevance
“…It is also likely that healthcare data will become accessible via standardized open software interfaces (apps) to researchers (and patients) with a focus on ‘efficacy, accuracy, utility, safety, privacy and security’ features. 34 …”
Section: Role Of Electronic Medical Records (Emr) and Ehealthmentioning
confidence: 99%
“…It is also likely that healthcare data will become accessible via standardized open software interfaces (apps) to researchers (and patients) with a focus on ‘efficacy, accuracy, utility, safety, privacy and security’ features. 34 …”
Section: Role Of Electronic Medical Records (Emr) and Ehealthmentioning
confidence: 99%
“…Any technologies incorporated into the system should be sustainable yet flexible to allow for substitut ability as the situation demands. Mandl and colleagues have proposed an ecosystem for apps that would inter face with electronic medical record systems 107 . These apps operate as 'side cars' that inter digitate with an electronic medical record system to provide a user interface that can display data and transfer informa tion, such as recom mendations for practice on the basis of prediction algorithms.…”
Section: Precision Participant Descriptormentioning
confidence: 99%
“…This change, along with the implementation of modern authorization (OAuth2) and authentication (OpenID Connect) protocols, led to the creation of SMART on FHIR [40]. SMART on FHIR has become increasingly recognized as the preferred solution to enable app-based health information tools [41,42]; the SMART app gallery now has 46 apps, the majority of which are conformant to SMART on FHIR specifications (https:// gallery.smarthealthit.org/). Over the past two years, a number of studies have demonstrated SMART on FHIR being implemented in a variety of high-impact settings.…”
Section: The Health Level 7: Fast Healthcare Interoperability Resourcmentioning
confidence: 99%